Communication—Electrochemical Impedance Signature of a Non-Planar, Interdigitated, Flow-Through, Porous, Carbon-Based Microelectrode. Issue 16 (1st January 2019) - Li, Zhenglong; Cheng, Yu-Hsuan; Feng, Lixin; Felix, De Dios; Neil, Jacob; Antonio, Reis Moura Pedro; Rahman, Maryom; Yang, Juliana; Azizighannad, Samar; Mitra, Somenath; Basuray, Sagnik
Abstract : Top and bottom microelectrode glass slide sandwiches a channel made of adhesive tape and packed with reduced graphene oxide to make a new non-planar interdigitated microfluidic device. Novel device integration allows packing of any transducer material at room temperature with no instrument. Electrical impedance spectroscopy signal is stable over long times, fits an equivalent circuit with well-defined circuit elements. Flow visualization concurs that electric double-layer signal shifts to high frequency due to disruption of the diffusive process from increased convective flow. Charge transfer resistance appears at higher frequencies making the device rapid with high signal to noise ratio.